Knowledge and practice of intermittent fasting: a cross-sectional study among university students in the United Arab Emirates - Sarah Imran Zahid; Mahnoor Dilawar; Fatima Garba Tahir; Tala Tarek Mousa; Nadia Imran Zahid; Jayadevan Sreedharan (Medicinski glasnik, 2025)
Aim: Intermittent fasting is a popular weight loss strategy that alternates between fasting periods and unrestricted eating. Research shows it can improve insulin resistance, lower HbA1c level, aid in weight management, and enhance cardiometabolic health. These effects can help address obesity, hypertension, and type 2 diabetes. Despite its popularity, research on intermittent fasting in the United Arab Emirates is sparse. This study aimed to evaluate the awareness and practice of different intermittent fasting regimens, including Alternate-Day Fasting, Modified Fasting, Time-Restricted Feeding, Ramadan Fasting, and Chinese Medical Nutrition Therapy, as well as to examine the relationship between intermittent fasting and obesity, hypertension, and type 2 diabetes. Methods: A cross-sectional study was conducted with 320 participants aged ?18 years, irrespective of gender or nationality. An approval was obtained from the Institutional Review Board, and informed consent was secured. Data were collected via a validated questionnaire on Google Forms, covering sociodemographic details, knowledge and practice of intermittent fasting, information sources, and health conditions. Results: A total of 270 (87.4%) of participants were aware of intermittent fasting, and 149 (55.2%) practiced it. There was no significant link between knowledge and practice, but 29 (78.4%) of practitioners associated intermittent fasting with obesity. Among those with chronic conditions, 23 (91.2%) experienced positive changes. Conclusion: Despite the high awareness of intermittent fasting, individual beliefs influence its practice. The identified association between obesity and positive changes in those with chronic conditions implies potential benefits.
Keywords: dietary practices; health behaviour; health promotion; obesity; type 2 diabetes